Are different generations of female employees trapped by work-family conflicts? A study on the impact of family-supportive supervisor behavior on thriving at work - Zhao, Xiao; Zhang, Tian; Choi, Myeongcheol; Xu, Jingyi (Frontiers in Psychology, 2024)
How to maintain female employees' work vitality and continuous learning is an issue that organizations need to explore continuously. This study focuses on professional women in China. Using Amos26.0 and SPSS25.0, it investigates the direct impact of family-supportive supervisor behavior (FSSB) on thriving at work and the mediating effect of work-family balance. Moreover, it explores the differences in direct and mediating effects of FSSB among different generations. The results show that FSSB has a significant positive impact on female employees' thriving at work, and work-family balance plays a mediating role. After distinguishing different generations, work-family balance partially and fully mediates the effect for "post-70s" and "post-80s" employees, respectively. However, it does not have a mediating effect for the "post-90s" employees indicating the existence of generational differences. The conclusions enrich the empirical research from the perspective of generational differences, which were less explored in previous studies. From a practical standpoint, this study provides valuable insights for organizations to improve the thriving at work of female employees.